2021
DOI: 10.14202/vetworld.2021.3170-3174
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of culling reasons during the breeding cycle and lifetime performance: The strategy to remove crossbred Landrace and Large White sows under tropical climate

Abstract: Background and Aim: Sow culling is an important practice in commercial swine production because it is directly associated with the economic efficiency of the breeding herd. This study was conducted to analyze the reasons for sow culling and quantify the factors affecting culling in crossbred Landrace and Large White sows under tropical climate. Materials and Methods: A total of 4887 culled sows from one parent stock farm located in Ratchaburi province, Western Thailand, were examined in this study. Culling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Reproductive failure (RF) is an unplanned sow removal, and Boripun et al [ 37 ] recently recommended the need to further investigate this RF removal. The study found that did not conceive was the major cause of RF removal at 30.7% (11,638/37,852).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproductive failure (RF) is an unplanned sow removal, and Boripun et al [ 37 ] recently recommended the need to further investigate this RF removal. The study found that did not conceive was the major cause of RF removal at 30.7% (11,638/37,852).…”
Section: Discussionmentioning
confidence: 99%
“…Frequency (number and percentage) of different causes of reproductive failure per parity of nurse sows(37,852). Chi-square test χ 2 = 352.480; df = 25; p < 0.001; Contingency Coefficient: 0.096.…”
mentioning
confidence: 99%